A method for Identifying sensitivity of marine benthic invertebrates to ocean acidification through a biological traits approach. (24th August 2022) - Gray, P; Garcia, C; Robinson, C; Bremner, J
Abstract: Ocean acidification poses a major threat to the structure and diversity of marine ecosystems. The marine seabed sustains important ecosystem functions, and so understanding the sensitivity to increased pCO2 within benthic invertebrates is critical for informing future management strategies. Here, we explore a traits-based approach for estimating the sensitivity of benthic taxa to ocean acidification, using data from the western area of the North Sea. We selected 56 taxa across 11 taxonomic groups representative of the various habitats found in the region. Biological traits considered sensitive to elevated pCO2 were identified from literature review, and the taxa were scored for each trait to produce a total relative sensitivity (TRS) index. We investigated differences in sensitivity between the taxa and across habitats and explored whether sensitivity was spatially aggregated. Our analyses indicated that benthic species are sensitive to acidification, with 51% of the taxa scoring in the top three TRS bands overall, and hot spots of sensitivity being more widely distributed across the region than corresponding "cold spots" (low sensitivity). The opportunities and limitations of the approach are discussed.